Answer:
<em>The cost of 10 cm and 70 cm are £0.55 and £3.85 respectively.</em>
Step-by-step explanation:
Material for a dress costs £5.50 per meter.
We know that, <u>1 meter = 100 cm</u>.
Suppose, the cost of 10 cm material is
and the cost of 70 cm material is ![y](https://tex.z-dn.net/?f=y)
Now, <u>according to the ratio of "cost" to the "length of material"</u> , we will get.......
![\frac{x}{10} =\frac{5.50}{100}\\ \\ 100x=10*5.50=55\\ \\ x=\frac{55}{100}=0.55](https://tex.z-dn.net/?f=%5Cfrac%7Bx%7D%7B10%7D%20%3D%5Cfrac%7B5.50%7D%7B100%7D%5C%5C%20%5C%5C%20100x%3D10%2A5.50%3D55%5C%5C%20%5C%5C%20x%3D%5Cfrac%7B55%7D%7B100%7D%3D0.55)
and
![\frac{y}{70} =\frac{5.50}{100}\\ \\ 100y=70*5.50=385\\ \\ x=\frac{385}{100}=3.85](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B70%7D%20%3D%5Cfrac%7B5.50%7D%7B100%7D%5C%5C%20%5C%5C%20100y%3D70%2A5.50%3D385%5C%5C%20%5C%5C%20x%3D%5Cfrac%7B385%7D%7B100%7D%3D3.85)
So, the cost of 10 cm material is £0.55 and the cost of 70 cm material is £3.85
Answer:
D.
Step-by-step explanation:
Remember that the limit definition of a derivative at a point is:
![\displaystyle{\frac{d}{dx}[f(a)]= \lim_{x \to a}\frac{f(x)-f(a)}{x-a}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%7B%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%28a%29%5D%3D%20%5Clim_%7Bx%20%5Cto%20a%7D%5Cfrac%7Bf%28x%29-f%28a%29%7D%7Bx-a%7D%7D)
Hence, if we let f(x) be ln(x+1) and a be 1, this will yield:
![\displaystyle{\frac{d}{dx}[f(1)]= \lim_{x \to 1}\frac{\ln(x+1)-\ln(2)}{x-1}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%7B%5Cfrac%7Bd%7D%7Bdx%7D%5Bf%281%29%5D%3D%20%5Clim_%7Bx%20%5Cto%201%7D%5Cfrac%7B%5Cln%28x%2B1%29-%5Cln%282%29%7D%7Bx-1%7D%7D)
Hence, the limit is equivalent to the derivative of f(x) at x=1, or f’(1).
The answer will thus be D.
Answer:
CT
Step-by-step explanation:
The diameter is the longest possible line through the sphere and passes through the center.
Answer:
1200 in³
Step-by-step explanation:
V= l×w×h
they gave you l×w which is 200.
200×6= 1200
The simplified version of this x-2z
Step-by-step explanation:
You need to start by combining like terms. You can start with the terms that have the variable x in them. By combining those terms, the equation becomes x+3y-z-3y-z.
From here, you can combine the terms 3y and -3y, which bring the equation to x-z-z.
From here, combine the terms with the variable z. This would bring the equation down too x-2z, your final answer.